DIGITAL TRANSFORMATION AS A DRIVER OF COMPETITIVENESS OF ENTERPRISES IN CONDITIONS OF ECONOMIC INSTABILITY (INNOVATIVE ECONOMY, 2025)
Lisnyi A.Ya.  DIGITAL TRANSFORMATION AS A DRIVER OF COMPETITIVENESS OF ENTERPRISES IN CONDITIONS OF ECONOMIC INSTABILITYPurpose. The aim of the article is a comprehensive assessment of the digital transformation of Ukrainian enterprises as a key factor in ensuring their competitiveness in conditions of economic instability and martial law.Methodology of research. General scientific and special methods were used in the research process, in particular: induction and deduction – at the stage of collecting, systematizing and processing the necessary information; tabular – for a visual presentation of systematized information, abstract and logical – for the formation of theoretical conclusions. The information basis of the research was statistical data of the State Statistics Service of Ukraine for 2018–2024.Findings. As a result of the study, an analytical review of the current state of digital transformation of Ukrainian enterprises in conditions of war was carried out, key digital tools used in business (AI, Big Data, cloud technologies, etc.) were summarized, and the prevailing directions of digitalization in Ukraine were identified. Based on official statistics of the State Statistics Service for 2018–2024, a quantitative analysis of the level of access of enterprises to the Internet, the use of cloud services, social media, big data analytics, and artificial intelligence was conducted. It is shown that despite the reduction in the total number of enterprises, the share of those implementing digital tools is growing. Special attention is paid to sectors in which digitalization has the greatest impact on maintaining the functioning of enterprises, in particular in the field of production and trade.Originality. For the first time, the work combines quantitative analysis of digitalization indicators with examples of real business functioning during the war, which made it possible to substantiate the conclusion about digital transformation as a tool for ensuring the stability and adaptability of enterprises.Practical value. The results can be used to formulate recommendations on the policy of digital support for business in emergency situations, as well as in the development of strategies for the digital transformation of enterprises in the post-war period.Key words: enterprise, war, cloud technologies, automation, artificial intelligence, digital economy.
Keywords: enterprise; war; cloud technologies; automation; artificial intelligence; digital economy